Identification of atrial fibrillation associated genes and functional non-coding variants - van Ouwerkerk, Antoinette F.; Bosada, Fernanda M.; van Duijvenboden, Karel; Hill, Matthew C.; Montefiori, Lindsey E.; Scholman, Koen T.; Liu, Jia; de Vries, Antoine A. F.; Boukens, Bastiaan J.; Ellinor, Patrick T.; Goumans, Marie José T. H.; Efimov, Igor R.; et al. (Nature Communications, 2019)
Disease-associated genetic variants that lie in non-coding regions found by genome-wide association studies are thought to alter the functionality of transcription regulatory elements and target gene expression. To uncover causal genetic variants, variant regulatory elements and their target genes, here we cross-reference human transcriptomic, epigenomic and chromatin conformation datasets. Of 104 genetic variant regions associated with atrial fibrillation candidate target genes are prioritized. We optimize EMERGE enhancer prediction and use accessible chromatin profiles of human atrial cardiomyocytes to more accurately predict cardiac regulatory elements and identify hundreds of sub-threshold variants that co-localize with regulatory elements. Removal of mouse homologues of atrial fibrillation-associated regions in vivo uncovers a distal regulatory region involved in Gja1 (Cx43) expression. Our analyses provide a shortlist of genes likely affected by atrial fibrillation-associated variants and provide variant regulatory elements in each region that link genetic variation and target gene regulation, helping to focus future investigations. The majority of disease-associated genetic variants lie in non-coding regions. Here the authors generated and compiled human transcriptomic, epigenomic and chromatin conformation datasets, to identify genes associated with atrial fibrillation and functional non-coding variants.